Serbian citizens’ awareness of consumer rights of tourists in the EU - Blesic, Ivana; Pivac, Tatjana; Veselinovic, Janko; Janicevic, Sava (Geographica Pannonica, 2019)
This paper analyses the protection of consumers of tourism services in EU law and consumer awareness in this domain in Serbia as a country currently negotiating accession to the EU. Consumer rights in EU tourism are defined by directives and regulations. This paper shall separately analyse two directives and one regulation that directly pertain to the protection of consumers of tourism services. Most legal sources are the codification of business practices of tourist organizations within the EU, but a part of mandatory provisions is the result of the need to protect consumers of tourism services in the domains of tourism in which they are most exposed to violation of their rights. For the needs of this paper, the survey was carried out on the territory of the Republic of Serbia, for the purpose of obtaining information on citizens’ awareness of the rights of consumers of tourism services in EU countries. The main aim of this study is to determine how well informed the citizens of Serbia are regarding consumer rights in tourism and legislation that governs those rights.